Bushen Zhuyun Decoction Improves Endometrial Receptivity by Inhibiting NF-κB/NLRP3 Signaling Pathway - Wang, Xiaolan; Tong, Yun; Zhang, Haidong; Zou, Yeting; Ding, Yinyin; Liu, Bei; Zhou, Weiye; Shan, Jinjun; Ji, Jianjian; Su, Wenren; Liu, Yinyin; Zhou, Huifang (Combinatorial Chemistry & High Throughput Screening, 2025)
ObjectiveBushen Zhuyun Decoction (BSZY), a traditional Chinese herbal prescription has shown promising effects on gynecological infertility, but the mechanism for endometrial receptivity is still unclear. This study aimed to investigate the regulatory effects of BSZY on endometrial receptivity, which plays a key role in colonization of embryo, and its regulatory mechanisms associated with NF- κB/NLRP3 pathway.MethodsSD rats at reproductive age with affected endometrial receptivity was established using mifepristone (RU486), and the regulatory effects of BSZY on endometrial receptivity were evaluated by H&E staining, and changes in sex hormones by ELISA and Western blot. Moreover, human endometrial RL95-2 cells were treated with H2O2, and inflammatory cytokines in rats and RL95-2 cells were analyzed by ELISA. The activation of NF-κB/NLRP3 signaling pathway in RL95-2 cells were characterized using immunofluorescence and Western blot. Mitochondrial morphology and function in RL95-2 cells were observed by transmission electron microscope and cell mitochondrial stress test.ResultsBSZY increased uterine endometrial thickness and attenuate histopathological changes induced by RU486. BSZY can regulate endometrial estrogen receptor and progesterone receptor, and the levels of sex hormones and inflammatory cytokines in pregnant rats. BSZY-containing serum also showed strong anti-inflammatory and cytoprotective effects in vitro. In addition, BSZY-containing serum inhibited the activation of NF-κB/NLRP3 signaling pathway, and improve mitochondrial morphology and function in RL95-2 cells.ConclusionBSZY can improve endometrial receptivity, potentially by improving mitochondrial morphology and function to inhibit the activation of NF-κB/NLRP3 signaling pathway in endometrial cells, thus regulate inflammation to improve endometrial receptivity.
Keywords: Endometrial receptivity